Insulin resistance increases the risk of incident type 2 diabetes mellitus in patients with non‐alcoholic fatty liver disease. Issue 3 (20th July 2017) - Seko, Yuya; Sumida, Yoshio; Tanaka, Saiyu; Mori, Kojiroh; Taketani, Hiroyoshi; Ishiba, Hiroshi; Hara, Tasuku; Okajima, Akira; Umemura, Atsushi; Nishikawa, Taichiro; Yamaguchi, Kanji; Moriguchi, Michihisa; et al.
Abstract : Aim: Type 2 diabetes mellitus (T2DM) is a major complication of patients with non‐alcoholic fatty liver disease (NAFLD). The aim of this retrospective study is to determine the risk factors for development of T2DM in patients with biopsy‐proven NAFLD. Methods: One hundred and sixty two consecutive patients with biopsy‐proven NAFLD who received a 75‐g oral glucose tolerance test were enrolled as the total cohort. Among them, we analyzed 89 patients without T2DM diagnosed by oral glucose tolerance test to estimate the cumulative rate for development of T2DM as the follow‐up cohort. Results: Of 162 patients, the glucose tolerance pattern were DM in 45 patients (27.8%), impaired glucose tolerance in 68 (42.0%), and normal glucose tolerance in 49 (30.2%). Patients with NAFL tended to be more likely to have normal glucose tolerance than those with non‐alcoholic steatohepatitis (NASH). The serum levels of pre‐ and post‐load insulin were significantly higher in the NASH group. Of 89 patients without T2DM, 13 patients newly developed T2DM during a follow‐up period of 5.2 years. The cumulative rate of T2DM incidence was 8.8% at the end of the 5th year and 23.4% at the end of the 10th year. Multivariate analysis identified homeostasis model of assessment – insulin resistance (≥3.85, hazard ratio 40.1, P = 0.033) as an independent risk factor for development of T2DM. Conclusions: Patients with NASH have an underlying potential of glucose intolerance. In NAFLD patients, insulin resistance is the most important risk factor for the incidence of T2DM. Appropriate therapy against insulin resistance could be needed for patients with NAFLD to prevent development of T2DM.